Temperature effect on deformation response in austenitic stainless steel - Barannikova, Svetlana A. 1971- (Defect and diffusion forum)
Stress-strain behavior of austenitic stainless steel grade AISI 304 was investigated by means of uniaxial tensile tests and magneto-phase analysis. The test materials were strained in tension within the temperature range of-100 ≤ T ≤ +100 °C. According to the results, intensive strain hardening occurs in austenitic stainless steel when strain-induced α'-martensite is present in the material, and stress-strain behavior is associated with the increase yield strength and tensile strength with decreasing temperature. The analysis of the hardening kinetics reveals that kinetics are affected by the temperature and by the amount of α'-martensite content